Implementasi Metode Pembelajaran Value Clarivication Technique (VCT) Pada Mata Pelajaran Akidah Akhlak Dalam Meningkatkan Nilai Akhlak Siswa Di Madrasah Tsanawiyah Nurul Ulum Karang Manggis Rombuh Palengaan Pamekasan - Nurul Latifah; Moh Fadiluddin; Siti Hotijah; ubaidillah ubaidillah; Ainul Mukarromah (Institut Kariman Wirayudha Sumenep, 2023)
The Effectiveness of the Implementation of the Value Clarification Technique (VCT) Learning Method in the subject of faith and morals in improving students' moral values ​​at the Nurul Ulum Karang Manggis Rombuh Palengaan Pamekasan with the formulation of the problem 1) how is the effectiveness of the Implementation of the Value Clarification Technique (VCT) Learning Method in the subject of faith and morals in improving students' moral values ​​at the Nurul Ulum Karang Manggis Rombuh Palengaan Pamekasan Middle School. 2) What are the supporting and inhibiting factors for the implementation of the Value Clarification Technique (VCT) Learning Method in the Subject of Faith and Morals in Improving Students' Moral Values ​​at the Nurul Ulum Karang Manggis Rombuh Palengaan Pamekasan Middle School? The research method used in this study is a qualitative descriptive approach where the research results obtained are in the form of descriptive data, the data sources of this study are the principal, teachers of the subject of aqidah and akhlak, and also students. Data analysis was carried out using a qualitative descriptive method by reducing data, presenting data, and verifying the data obtained. The results of the research that the researcher has done show that the implementation of the value clarification technique method is effective because during the subject of faith and morals using this method, students are seen to be active in expressing their opinions politely, have a respectful attitude when their friends express their opinions and discuss and an honest attitude that they have when clarifying moral values ​​that are in accordance with the values ​​they have in everyday life. The supporting factors for the Value Clarification Technique (VCT) method are the existence of teachers who have broad insight and have good moral values ​​because in the subject of faith and morals, it contains both commendable and reprehensible behavior, so if the teacher has an exemplary nature, it will be a good reflection as well, such as the teacher never plays favorites against those who have opinions and respects every opinion they express and the existence of adequate media also supports the effectiveness of the application of the method. The inhibiting factors are the lack of understanding of students regarding the importance of moral values ​​so that there are still some children who do not listen, busy themselves during learning.